Influence of nutritional facts label on individual purchasing decisions of pre-packaged food Items in Ibadan metropolis, Oyo State, Nigeria (2020)
The surge, in recent times, in the rate at which people suffer from various health problems such as high blood pressure, high body mass index, high cholesterol, and high blood glucose among others, usually resulting from poor diet, has been very alarming. This study examined the influence of nutritional facts label on the individual purchasing decisions of pre-packaged food items in Ibadan metropolis, Oyo State, Nigeria. Despite the high level of awareness of nutritional facts label, choices were often dependent on other factors such as price, quality and taste, mainly because most of the consumers did not understand the information on the nutritional labels and were not able to relate the information to their health. However, among those that highly used nutritional facts label in making purchasing decisions of pre-packaged foods, middle aged, highly educated, married females were prominent. Consumers should be enlightened on the use of labelling information in making informed decisions and the possible health implications of neglecting such practice.